THE EXTENT OF THE COMMITMENT OF JORDANIAN COMMERCIAL BANKS TO THE STRATEGIES OF FACING FINANCIAL AND ECONOMIC GLOBALIZATION: EMPIRICAL STUDY - Mohanad Fsyiz Saleem Al-dweikat (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This research aims to identify the extent of the commitment of Jordanian commercial banks to strategies to confront financial and economic globalization. The study population may have consisted of all the 23 banks listed in the Amman Stock Exchange, according to what was mentioned in the monthly report of the Amman Stock Exchange for the month of December of the year 2020. As for the study sample, (100) respondents were selected from financial managers and accountants. Workers in the finance and investment departments and the human resources department work in these banks. The questionnaire was used as a tool for collecting primary data. The results showed that Jordanian commercial banks apply financing and investment strategies, marketing strategy and human resources strategy to face financial and economic globalization to a high degree. In light of this, appropriate recommendations were presented that would deal with a topic related to the commitment of Jordanian commercial banks to implement strategies to confront financial and economic globalization.